The important practical results and modern lines in studying diseases of the stomach and duodenum (Review of the Seventeenth Russian Gastroenterological Week proceedings, October, 10–12, 2011, Moscow) - I. V. Mayev; A. A. Samsonov; N. G. Andreyev; D. N. Andreyev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze and present in brief contents of original materials, The Seventeenth Russian Gastroenterological Week (October, 10–12, 2011, Moscow,) published in the section «Diseases of the stomach and duodenum» (Ros. zhurn..gastroenterol. gepatol. koloprotol. – 2011. – Vol. 21, N 5. – Suppl. 38).Original positions. The further accumulation and analysis of data on etiology, pathogenesis and clinical features of diseases of the stomach and duodenum based on the advanced methods of investigation. Elements of diagnostic concepts and therapeutic approaches for this group of diseases of gastro-intestinal tract (GIT) are modified. The most actual issues are: Helicobacter-associated pathology of the stomach, NSAID-related gastropathy and their complications and issues of early diagnostics of premalignant changes and stomach cancer.Conclusion. Diseases of the stomach and duodenum remain significant problem of gastroenterology, despite of significant advances in last decades in diagnostics and treatment of these diseases of GIT.